Impact of Lead (Pb) Exposure on Hematological Parameters, hs-CRP, Ferritin, and Oxidative Stress (MDA) in Battery Factory Workers - Maryam, Nur Siti; Susilowati, Indah Tri; Rahayu, Kanti; Nur Saputro, Rizki Alifah (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2025)
Exposure to lead in the workplace is common, with most employers and workers unaware of its adverse health effects. This study examines the relationship between blood lead levels in battery factory workers and health examination results such as Hematology profile (Hemoglobin level, Leukocyte count, Hematocrit Level, Platelet count, Erythrocyte Count, MCV, MCH, and MCHC), malondialdehyde (MDA), ferritin, and hs-CRP. The samples of this study were 25 blood samples of battery factory employees in Jakarta who were older than 40 years and had worked for more than 1 year. Workers' blood samples were collected using vacuum tubes and placed in ice boxes to be sent to PT Petrolab Service Laboratory for blood lead level examination, Citama Hospital Laboratory Unit for blood profile examination, ferritin level, and hs-CRP value, and Prodia Jakarta Clinical Laboratory for MDA level examination. Bivariate analysis examined the relationship between lead levels, blood profile, ferritin levels, MDA levels, and hs-CRP values. Using the entered formula, multivariate analysis was used to test the relationship between lead levels and blood profile, ferritin levels, MDA levels, and hs-CRP values. The significance level used to test the significance of the relationship was <0.05. The bivariate test results showed there was a correlation between blood lead levels and hs-CRP levels (P=0.000), MDA levels (P=0.000), ferritin levels (P=0.000), Hb levels (P=0.000), hematocrit levels (P=0.006), MCV value (P=0.000), and MCH value (P=0.004). In contrast, Multivariate analysis showed lead levels significantly correlated with MDA level (P=0.014), ferritin level (P=0.005), and MCV value (P=0.013). Blood lead levels should be controlled to reduce the risk of oxidative stress and its impact on health, and it is hoped that workers in contact with lead will place more emphasis on occupational safety and health.